Investigation of Convective Heat Transfer and Friction Factor in Corrugated Channels with Different Inclination Angles Using Computational Fluid Dynamics - Aslan, Erman; Kepekci, Haydar (Journal of Advanced Thermal Science Research, 2021)
Convective heat transfer and friction factor properties for periodic undulating channels are numerically investigated. The finite volume method (FVM) was used in the numerical study. Three different Reynolds averaged numerical simulation (RANS) based turbulence models, shear stress transport SST k-ω and transition SST model were used and compared with each other. Two different channels were used; the first geometry is a sharp corrugated channel with a 30° inclination angle, and the second geometry is a sharp corrugated channel with a 45° inclination angle. The Reynolds number varies in the range of 2000-7500. The Prandtl number was kept constant at 0.7. Nusselt number, friction factor, Reynolds number, and variations of the good factor were investigated. The effect of inclination angle and pitch are discussed.